THE FIRST FINDS OF UPPER CRETACEOUS RHYNCHOLITES OF THE GENUS AKIDOCHEILUS TILL - Komarov V.N. (My University, 2003)
A new rhyncholite species, Akidocheilus (Akidocheilus) costatisulcatus, is described from the Biyuk-Yanyshar Ridge. This is the first record of rhyncholites from the Lower Callovian of the Crimean Mountains.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая